PERANCANGAN SISTEM INFORMASI PENGARSIPAN DATA SISWA BERBASIS WEBSITE PADA MA NURUL KHOIROH KABUPATEN BANYUWANGI - Ifda Khnaifatu Zahro; Irma Yunita; Novia Rofiatul Chasanah (CV. Denasya Smart Publisher, 2025)
The student data archiving system at MA Nurul Khoiroh, Banyuwangi, is still managed manually using printed documents, which often causes problems such as data duplication, recording errors, and delays in information retrieval. This study aims to design a web-based student data archiving information system to improve efficiency, accuracy, and security in archive management. The research method includes observation, interviews, and documentation studies with a qualitative approach, while the system development process applies the Waterfall model consisting of requirement analysis, system design, implementation, testing, and maintenance. The results indicate that the designed system can facilitate the admin in inputting, editing, deleting, searching, and managing student data archives in a more structured and integrated manner. The implementation of this web-based information system makes the student data archiving process at MA Nurul Khoiroh faster, more accurate, and supportive of transparency and administrative effectiveness.